Status of Water Supply in Parts of Umuahia South Local Government Area, Abia State, Nigeria: A Look at Alternatives - S. A., Ngah; U.N., Ekpebegh (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2016)
The study investigated the water supply sources in Old Umuahia semi-urban district in Abia State, Nigeria. Emphasis was on the quality and quantity of available water sources. Some socio-economic considerations such as family sizes, proximity of source, quality and quantity of water actually used per day as compared with quantity required per day were all evaluated. Water supply shortfall was hence evaluated and quantified. Different sources of water in use were evaluated. They include motorized boreholes, Springs, Streams, commercial water vendors and harvested rainwater. The study showed that the majority of residents had bread winners who were civil servants (48%) with an average family size of 5-8 people. Most people practice conjunctive water use of water combining more than one source with comparative advantages. 89% of the people depend on water boreholes for their drinking water supplies. Available hydrogeological data from the area were reviewed. The area was found to be underlain by a prolific aquifer capable of sustainably supplying the area. Water samples were collected from the different water sources and analysed for concentration of key physico-chemical parameters such as pH, Dissolve d Oxygen, conductivity, turbidity, total dissolved solids, total hardness, chloride, salinity, total alkalinity, copper, iron, manganese, sulphate, chromium, colour and zinc. The results were compared with World Health Organisation (WHO) standards for domestic water supply. From the results, water in the area was found to be acidic with pH values ranging from 4.9 to 5.15 (mean value, 5.02). All the other physico-chemical parameters showed values that plot within the limit of acceptability of WHO standards except for two boreholes sources, two streams sources and samples from the commercial water vendors whose water samples indicated serious bacteriological contamination. Supplies from groundwater sources is of highest quality. Since the area is underlain by aquifers with excellent water yielding properties, the studyrecommended the development of water supply in the area mainly from groundwater sources. This will require additional hydrogeological studies to determine the number, location and depths of new boreholes to serve the domestic water demands of the inhabitants of the area. Existing four boreholes are grossly inadequate to meet and sustain the domestic water needs of about 8000 people who presently inhabit the area. Similarly, people should be discouraged from using the water from commercial water vendors for domestic purposes. This will drastically reduce the incidence of water-borne diseases in the area.